Nanolipoprotein particles for co-delivery of cystine-knot peptides and Fab–based therapeutics. Issue 13 (4th June 2021) - Darwish, Martine; Gao, Xinxin; Shatz, Whitney; Li, Hong; Lin, May; Franke, Yvonne; Tam, Christine; Mortara, Kyle; Zilberleyb, Inna; Hannoush, Rami N.; Blanchette, Craig
Abstract : Nanolipoprotein particles (NLPs) have been evaluated as a delivery vehicle for a variety of molecules of therapeutic interest. Abstract : Nanolipoprotein particles (NLPs) have been evaluated as an in vivo delivery vehicle for a variety of molecules of therapeutic interest. However, delivery of peptide-like drugs in combination with therapeutic Fabs has not yet been evaluated. In this study, we describe the development and characterization of cystine-knot peptide (CKP)-containing NLPs and Fab–CKP-NLP conjugates. CKPs were incorporated into NLPs using a self-assembly strategy. The trypsin inhibitor EETI-II, a model CKP, was produced with a C16 fatty acyl chain to enable incorporation of the CKP into the lipid bilayer core during NLP assembly. The CKP-NLP retained trypsin inhibitory function although the overall activity was reduced by ∼5 fold compared to free CKP, which was presumably due to steric hindrance. The NLP platform was also shown to accommodate up to ∼60 CKP molecules. Moreover, the stability of the CKP-NLP was comparable to the NLP control, displaying a relatively short half-life (∼1 h) in 50% serum at 37 °C. Therapeutic Fabs were also loaded onto the CKP-NLP by introducing thiol-reactive lipids that would undergo a covalent reaction with the Fab. Using this strategy, Fab loading could be reliably controlled from 1–50 Fabs per CKP-NLP and was found to be independent of CKP density. Surprisingly, Fab incorporation into CKP-NLPs led to a substantial improvement in NLP stability (half-life > 24 h) at 37 °C; also, there was no reduction in CKP activity in the Fab–CKP-NLP conjugates compared to CKP-NLPs. Altogether, our data demonstrate the potential of NLPs as a promising platform for the targeted or multidrug delivery of peptide-based drug candidates in combination with Fabs.